ANALISIS DAN PERANCANGAN SISTEM INFORMASI LAYANAN PERSIDANGAN BERBASIS WEB PADA PENGADILAN AGAMA JAMBI KELAS IA - Yanti, Elvi; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2019)
Jambi Religion Court is one of the judicial bodies that has the duty and authority to examine, decide, and settle cases atthe first level between people who are Muslim in the field of marriage, inheritance, wills, and grants. The issue that hasalways surfaced in the community regarding service to the Jambi Religious Court is the delay in the settlement of the caseprocess. This is caused by the lack of information obtained by litigant parties, the difficulty in accessing courtinformation services that are still closed, the court is slow in providing information because the information provided stillrelies on summons which sometimes is not conveyed to the parties thus making the trial delayed again and resulted in thedelay in the process of settling the case. The solution offered is a change in the information system that is displayed basedon the website, where through this system makes it easy for visitors to get information quickly. The system modeling toolused is UML (Unified Modeling Language). The output produced is in the form of prototypes with trial schedule reports,case reports, court case reports, and case reports entered monthly